Effects of temperature, water content, pH and soil sterilization on the degradation of CP4-EPSPS protein released from herbicide-tolerant corn leaves in the soil. (May 2018) - Zeng, Xing; Wang, Kang; Feng, Chenchen; Song, Xinyuan; Qi, Fengkun; Zhang, Lin; Dong, Ling; Zhou, Yu; Liu, Xianjun; Wang, Zhenhua; Di, Hong
Abstract: Determining the influence of soil environmental factors on the degradation of CP4-EPSPS protein from herbicide-tolerant (HT) corn residue is crucial for assessing the ecological risks of commercialized transgenic crops. We investigated the effects of soil temperature (15 °C, 25 °C, 35 °C), soil water content (20%, 33%, 50%), pH (5.0, 7.0, 9.0) and soil treatment (not sterilized, sterilized) on the degradation of CP4-EPSPS protein released from the leaves of the HT corn variety CC-2. An exponential model (first order) was fitted to the degradation dynamics of CP4-EPSPS protein and used to estimate the time required for 50% degradation (DT50) and for 90% degradation (DT90). The results showed that CP4-EPSPS protein released from CC-2 leaves presented similar degradation features in all treatments: a sharp decrease in the early stage followed by a slow decline in the middle and late stages was observed. In the late stage (more than 120 d after the experiment started), CP4-EPSPS protein released from CC-2 leaves was not detected in the soil using enzyme-linked immunosorbent assay (ELISA) tests. The DT50 values of CP4-EPSPS protein released from CC-2 leaves ranged from 0.92 d to 11.32 d, and the DT90 values ranged from 3.11 d to 36.59 d. The results suggest that soil temperature and soil sterilization significantly affected the degradation of CP4-EPSPS protein. Faster degradation rates were observed at higher temperature under non-sterilized conditions, but soil water content and pH did not clearly affect the degradation of CP4-EPSPS protein. These findings suggest that under appropriate soil temperature conditions, CP4-EPSPS protein from HT corn residue will not persist or accumulate in the soil. Highlights: CP4-EPSPS protein degraded rapidly in early stage but slowly in mid and late stage. Degradation dynamics of CP4-EPSPS protein can be estimated by exponential model. Temperature was major factor that affected the degradation of CP4-EPSPS protein.